Private Infrastructure : Activity Down by 30 Percent in 2002 - World Bank (Washington, DC, 2012)
Over the past decade most developing economies have involved the private sector in providing infrastructure services. Indeed, between 1990 and 2002, 136 low- and middle-income countries introduced private participation in infrastructure sectors-65 of them in at least three sectors. During that period the private sector took over the operating or construction risk, or both, for more than 2,600 astructure projects in developing countries, attracting investment commitments of more than US$800 billion. These projects have been implemented under schemes ranging from management contracts to concessions to divestitures to greenfield build-operate-transfer or build-operate-own projects. Annual investment flows to infrastructure projects with private participation grew strongly between 1990 and 1997, from US$18 billion to more than US$127 billion. Since then investment flows have gradually declined, except for a temporary recovery in 2000.